Deficient Pain Modulation in Patients with Chronic Hemiplegic Shoulder Pain. Issue 6 (11th January 2018) - Kashi, Yafit; Ratmansky, Motti; Defrin, Ruth
Abstract: Background: Hemiplegic shoulder pain (HSP) following stroke significantly affects the individual's function and quality of life. The mechanism of HSP is not clearly understood; hence, it is unclear why HSP resolves spontaneously or following routine care in some patients, while in others it becomes persistent. The aim was therefore to study whether HSP is associated with deficient pain modulation. Methods: Thirty post‐stroke patients—16 with HSP and 14 without HSP—and 20 matched controls participated. Pain adaptation and conditioned pain modulation (CPM) were measured as indicators of pain modulation, in the affected (hemiplegic) and contralateral shoulder as well as in the affected shin among post‐stroke patients, and in comparable body regions among controls. Post‐stroke patients also underwent functional and physical evaluation of the shoulder. Results: Pain adaptation was absent among HSP patients, in both the painful shoulder and the affected shin, but existed in the 2 control groups. In addition, the affected shoulder and shin among the HSP group had reduced thermal sensibility compared to the contralateral regions. CPM was similar across groups. Shoulder functional status and physical status were similar for the 2 post‐stroke groups. Conclusions: The results suggest that HSP is associated with a lack of pain adaptation, characteristic not only of the painful shoulder but also of the affected side. Although we cannot determine whether lack of pain adaptation precedes the HSP or results from it, interventions that enhance descending pain inhibition may improve management and prevent HSP chronification.